Pengembangan LKPD dengan Model PjBL untuk Menumbuhkan Karakter Senang Belajar Materi Perubahan Wujud Benda Siswa Kelas IV SD - Valentina Devi Centia Safety; Puji Purnomo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to develop and assess the quality of Student Worksheets (LKPD) based on Project Based Learning (PjBL) on the material of changes in the form of objects for grade IV elementary school students, in order to foster a character of enjoying learning in accordance with the Merdeka Curriculum. This study uses the Research and Development (R&D) method of the ADDIE model which includes five stages: Analyze, Design, Development, Implement, and Evaluate. The product was developed by involving four validators (two principals and two grade IV teachers) and was tested on 38 students. Data were collected through tests (pretest and posttest) and non-tests (observation, interviews, and questionnaires), then analyzed qualitatively and quantitatively. The results of the study showed that the Student Worksheets (LKPD) developed had